Generation of octree meshes with cut cells in multiple material domains - Chernyshenko, A.Yu. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2013)
An algorithm for the generation of octree meshes with cut cells generation in complex multiple material domains is proposed. The method of cell cutting is based on the cubical marching squares and multiple material marching cubes algorithms. The algorithm and mesh examples are analyzed.